ETHICS OF MEDICAL AUTHORSHIP - Javaid, Arshad (Journal of Postgraduate Medical Institute, 2015)
Ethics is an integral part of Medical practice. Bioethics,Research Ethics or even Ethics of Medical Authorshipall are of paramount importance. The subject of MedicalEthics is very much in vogue these days. Recent advancesin medicine and technological advances have highlightedthe ethical issues medical practice. Declarationof Helsinki, adopted in June 1994 and finally approvedin 2002 is a document of ethical principles in medicalresearch involving human subjects. This editorial will focusmainly on the ethics of medical authorship as wellas medical research.